Thermodynamics and kinetic analysis of membrane: Challenges and perspectives - Ahmad, Tausif; Rehman, Lubna M.; Al-Nuaimi, Reham; de Levay, Jean-Pierre Benjamin Boross; Thankamony, Roshni; Mubashir, Muhammad; Lai, Zhiping (Chemosphere (Oxford), 2023)
The ultimate structure of the membrane is determined using two important effects: (i) thermodynamic effect and (ii) kinetic effect. Controlling the mechanism of kinetic and thermodynamic processes in phase separation is essential for enhancing membrane performance. However, the relationship between system parameters and the ultimate membrane morphology is still largely empirical. This review focuses on the fundamental ideas behind thermally induced phase separation (TIPS) and nonsolvent-induced phase separation (NIPS) methods, including both kinetic and thermodynamic elements. The thermodynamic approach to understanding phase separation and the effect of different interaction parameters on membrane morphology has been discussed in detail. Furthermore, this review explores the capabilities and limitations of different macroscopic transport models used for the last four decades to explore the phase inversion process. The application of molecular simulations and phase field to understand phase separation has also been briefly examined. Finally, it discusses the thermodynamic approach to understanding phase separation and the consequence of different interaction parameters on membrane morphology, as well as possible directions for artificial intelligence to fill the gaps in the literature. This review aims to provide comprehensive knowledge and motivation for future modeling work for membrane fabrication via new techniques such as nonsolvent-TIPS, complex-TIPS, non-solvent assisted TIPS, combined NIPS-TIPS method, and mixed solvent phase separation. [Display omitted] •Review of modeling for membrane synthesis through NIPS and TIPS methods.•Discussion of macroscopic, mesoscopic, and molecular scales.•Analysis of limitations associated with different macroscopic transport models.•Provision of motivation for future modeling work in the field.•In-depth discussion of current difficulties faced in membrane synthesis.